ANALISIS AUDIT INVESTIGATIF PADA BADAN PENGAWASAN KEUANGAN DAN PEMBANGUNAN - Adib Muhammad Iyasy; Mohamad Khoiru Rusydi (JURNAL INFO ARTHA, 2025)
This study aims to analyze the implementation of investigative audits at the Financial and Development Supervisory Agency (BPKP), especially related to the use of investigative audit approaches, procedures, and techniques in order to uncover fraud. This research uses a qualitative method with a case study approach at the BPKP Representative of East Java Province. The research sources used interviews and documentation. The results showed that investigative audits at BPKP are specific only to prove the presence or absence of indications of corruption. The investigative audit approach used is the fraud theory approach. The lack of investigative audit assignments is due to the BPKP Representative of East Java Province being passive and the lack of public understanding. The investigative audit procedures used are divided into general procedures and special procedures. Investigative audit procedures cannot be done by sampling. Investigative audit techniques used must be more than one technique and one of the techniques used must be the clarification request technique. Limited authority needs to be anticipated with persuasive steps and additional audit techniques.